2005
DOI: 10.1111/j.1399-3038.2005.00301.x
|View full text |Cite|
|
Sign up to set email alerts
|

Three‐year follow‐up of clinical and inflammation parameters in children monosensitized to mites undergoing sub‐lingual immunotherapy

Abstract: Parallel follow-up of clinical and inflammatory markers during sub-lingual immunotherapy (SLIT) is highly beneficial. Twenty-four children (age 4-16) monosensitized to house dust mite were randomized to receive either active or placebo SLIT for 1 yr in a double-blind placebo controlled design (Marcucci et al., Allergy 2003: 58: 657-62). Thereafter, for 2 yr they all received active treatment. Symptom scores for rhinitis, asthma, and drug usage were daily recorded. Eosinophil cationic protein (ECP) and tryptase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 36 publications
4
40
1
Order By: Relevance
“…However, more recently, several studies have also shown efficacy using SLIT in pediatric and adult patients with asthma and/or rhinitis [26][27][28][29][30]. SLIT has been shown to reduce nasal symptoms and drug consumption in several of these studies.…”
Section: Introductionmentioning
confidence: 96%
“…However, more recently, several studies have also shown efficacy using SLIT in pediatric and adult patients with asthma and/or rhinitis [26][27][28][29][30]. SLIT has been shown to reduce nasal symptoms and drug consumption in several of these studies.…”
Section: Introductionmentioning
confidence: 96%
“…After a local allergen challenge, a significant increase in MCT was demonstrable in tear fluid only after 20 min [9,13] , and in nasal secretions only after 30 min [7] . Although MCT has a half-life of several hours, it is measurable only during a short period of time because saliva is swallowed and because tears and nasal secretions are removed quickly.…”
Section: Discussionmentioning
confidence: 99%
“…After a local allergen challenge, MCT concentrations also rise in nasal secretions [6][7][8] , tears [9] , bronchoalveolar lavage fluid [10] , and sputum [7] .…”
Section: Introductionmentioning
confidence: 99%
“…SCIT seems to be associated with a decrease in IL-4 and IL-5 production by CD4+ Th2 cells, and a shift towards increased IFN-gamma production by Thl cells (24,25). Few data concerning the immunologic changes induced by SLIT (40) are known and these studies have shown a relevant effect on the IgG4 response thus it could seem that SLIT does not consistently reduce the IgE production and increase the IgG4 synthesis (41,42). On the contrary, a decrease of serum IL-13 and of T-cell proliferative response (43) was demonstrated after SLIT therapy (44).…”
Section: Ig-e Mediated Mechanismmentioning
confidence: 99%